(untitled) (Journal of the College of Basic Education, 2022)
For as long as few decades, the anecdotal journalists have started portraying the presence of females’ experience which was previously anonymous and unimagined. Different basic attempts have been propelled, centering the eyes of the users, merging upon the universe of women. The authors began to investigate females’ battle for freedom in their works. The present article tackles the women characters and their identity. Further, this paper will try to answer the question wither V.S. Naipaul was a feminist or antifeminist? It highlights the position of female characters in the novel A House for Mr.Biswas by V.S. Naipaul.